Dysnatremias in Chronic Kidney Disease: Pathophysiology, Manifestations, and Treatment - Arzhan, Soraya; Lew, Susie Q.; Ing, Todd S.; Tzamaloukas, Antonios H.; Unruh, Mark L. (Frontiers in Medicine, 2021)
The decreased ability of the kidney to regulate water and monovalent cation excretion predisposes patients with chronic kidney disease (CKD) to dysnatremias. In this report, we describe the clinical associations and methods of management of dysnatremias in this patient population by reviewing publications on hyponatremia and hypernatremia in patients with CKD not on dialysis, and those on maintenance hemodialysis or peritoneal dialysis. The prevalence of both hyponatremia and hypernatremia has been reported to be higher in CKD patients than in the general population. Certain features of the studies analyzed, including variation in the cut-off values of serum sodium concentration ([Na]) that define hyponatremia or hypernatremia, create comparison difficulties. Dysnatremias in CKD patients are associated with adverse clinical conditions and mortality. Currently, investigation and treatment of dysnatremias in CKD patients should follow clinical judgment and the guidelines for the general population. Whether azotemia allows different rates of correction of [Na] in hyponatremic CKD patients and the methodology and outcomes of treatment of dysnatremias by renal replacement methods require further investigation. In conclusion, dysnatremias occur frequently and are associated with various comorbidities and with mortality in CKD patients. Knowledge gaps in their treatment and prevention call for further studies.